2017
DOI: 10.5194/acp-17-7891-2017
|View full text |Cite
|
Sign up to set email alerts
|

Optical, physical and chemical properties of aerosols transported to a coastal site in the western Mediterranean: a focus on primary marine aerosols

Abstract: Abstract. As part of the ChArMEx-ADRIMED campaign (summer 2013), ground-based in situ observations were conducted at the Ersa site (northern tip of Corsica; 533 m a.s.l.) to characterise the optical, physical and chemical properties of aerosols. During the observation period, a major influence of primary marine aerosols was detected (22-26 June), with a mass concentration reaching up to 6.5 µg m −3 and representing more than 40 % of the total PM 10 mass concentration. Its relatively low ratio of chloride to so… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 90 publications
1
9
0
Order By: Relevance
“…The two sources of combustion identified by PMF, i.e. biomass burning and anthropogenic sources, have previously been observed in background aerosols in Corsica (Arndt et al, 2017;Claeys et al 2017). Concerning major nutrients, P deposition is highly associated to biomass burning inputs out of the most intense dust deposition events.…”
Section: Source Apportionment and Background Depositionmentioning
confidence: 84%
See 1 more Smart Citation
“…The two sources of combustion identified by PMF, i.e. biomass burning and anthropogenic sources, have previously been observed in background aerosols in Corsica (Arndt et al, 2017;Claeys et al 2017). Concerning major nutrients, P deposition is highly associated to biomass burning inputs out of the most intense dust deposition events.…”
Section: Source Apportionment and Background Depositionmentioning
confidence: 84%
“…Thus, almost 50% of N fluxes is explained by the marine source. Several works observed that the depletion of chloride (Cl) and the simultaneous occurrence of NO3 in sea salt aerosol particles is due to the reaction between NaCl and HNO3 when maritime and anthropogenic air masses are mixed, in Mediterranean environments (Sellegri et al, 2001;Bardouki et al, 2003;Pey et al, 2009) and in particular in Corsica (Claeys et al, 2017). The contribution of marine source to N deposition is probably due to the deposition of these processed seasalt particles.…”
Section: Source Apportionment and Background Depositionmentioning
confidence: 99%
“…The biomass burning/waste source is mainly characterized by Cu, K, P, and Zn. K is commonly associated with waste/biomass burning or wood combustion (Dall'osto et al, 2013;. The maximum of this source deposition in summer, in spite of a minimum of rain, corresponds with the intense forest fires observed in the Mediterranean region in this period, and which impact the entire basin (Bossioli et al, 2016).…”
Section: Source Apportionment and Background Depositionmentioning
confidence: 99%
“…4.4.2). For organic aerosols, the gas-particle partitioning of the surrogates is computed using SOAP (Secondary Organic Aerosol Processor), assuming bulk equilibrium (Couvidat and Sartelet, 2015). The gas-particle partitioning of hydrophobic surrogates is modeled following Pankow (1994), with absorption by the organic phase (hydrophobic surrogates).…”
Section: Simulation Setups and Alternative Parameterizationsmentioning
confidence: 99%